Dynamical coupling of dilute magnetic impurities with quantum spin liquid state in the S = 3/2 dimer compound Ba3ZnRu2O9. (8th August 2018) - Yamamoto, Takafumi D; Taniguchi, Hiroki; Terasaki, Ichiro
Abstract: We have investigated the dilute magnetic impurity effect on the magnetic properties of a quantum spin liquid candidate Ba3 ZnRu2 O9 and a spin gapped compound Ba3 CaRu2 O9 . The magnetic ground state of each compound stands against 2% substitution of magnetic impurities for Zn or Ca. We have found that the magnetic response of these impurities, which behave as paramagnetic spins, depends on the host materials and the difference of the two manifests itself in the Weiss temperature, which can hardly be explained by the dilute magnetic impurities alone in the case of Ba3 ZnRu2 O9 . We consider a contribution from the Ru 5+ ions which would appear only in the substituted Ba3 ZnRu2 O9 and discuss a possible physical meaning of the observed Weiss temperature.